La présentation des objets africains dans DOCUMENTS (1929/1930), magazine illustré - Coline Bidault (Les Cahiers de l'École du Louvre)
Documents was a magazine published in 1929 and 1930. Co-edited by Georges Bataille and Carl Einstein, it was characterised by the multiplicity of the subjects covered as well as by the diversity of its collaborators. As it appeared when the reorganisation of the Musée du Trocadéro was being undertaken by Georges Henri Rivière and Paul Rivet, Documents allotted a great deal of space to ethnography. The theme of Africa is recurrent and many reproductions of African objects featured in the publication. But the objective of Documents was above all to break down the barriers between the various disciplines by adopting a particular aesthetic: the juxtaposition of a wide variety of methods, ideas, texts and images, as well as of ways of thinking about African objects, meant that these could be considered in ways that went beyond the classic opposition of ethnographical and aesthetic approaches.